AKTIVITAS ANTIOKSIDAN EKSTRAK DAUN SUJI (Pleomele angustifolia N.E. Brown) [Antioxidant Activity of Suji (Pleomele angustifolia N.E. Brown) Leaf Extract] - Endang Prangdimurti; Deddy Muchtadi; Made Astawan; Fransiska R Zakaria (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2006)
Numerous studies showed that chlorophyll and its derivatives had antioxidant activity. This research was conducted to obtain the chlorophyll-rich suji leaf liquid extract (SLE) and then to investigate the oral administration this extract on the antioxidant status by means of animal study. The use of Tween 80 0.75% in sodium citrate 12 mM solution as an extraction solution combined with 30 minutes incubation time at 70-75oC increased significantly the total chlorophylls content, the water-soluble chlorophylls content and the antioxidant activity of the yielded extract, compared to the suji leaf water-only extract. Two-month oral administration of SLE to male Sprague Dawley rats showed that the liver MDA level significantly decreased, and the liver catalase and superoxide dismutase antioxidant enzyme activities significantly increased compared to the control group. It was suggested that the chlorophyll content in SLE might increase the antioxidant status of animal tested.